The banking systems of Germany, the UK and Spain form a spatial perspective: Lessons learned and what is to be done? - Franz Flögel; Stefan Gärtner (Institut Arbeit und Technik (IAT), 2018)
This paper re-visits the state of decentralised banking in Germany, Spain and the UK. The cross-country comparison we conducted has identified Germany as having the most decentralised banking system, followed by Spain and the UK, as expected. The development of regional and double-purpose banks, i.e. savings and cooperative banks, mainly account for the differences in the degree of centralisation. Whereas no such bank exists in the UK any longer and real savings banks in Spain have almost disappeared, two decentralised banking groups with more than 1,400 savings and cooperative banks dominate business finance in Germany. Our comparison has identified three factors of success contributing to the persistence of decentralised banking: I. Short operational and (especially) functional distance and embeddedness in supportive regional bank associations. Short distances allow banks to capitalise on soft information advantages in lending, whilst banking associations also secure access to advanced banking knowledge for banks headquartered in peripheral regions. II. The development of "real" decentralised universal banking. Here, the time when regional savings and cooperative banks received the right to lend is crucial. Because it took them so long to get permission to offer loans, savings banks in Spain and the UK were latecomers to (business) lending, whereas lending had always been the business of German savings banks. Therefore, savings banks in the UK and Spain were not able to capitalise on soft and local information advantages in short distance lending. III. The interplay of the regional principle (regional market segregation), regional embeddedness and a national system that balances regional disparities. Together, these three factors help to make regional banks sufficiently successful, even in weak regions, and hinder competition between banks, thereby supporting meaningful cooperation in banking associations and relationship lending. Savings banks have never been as important in business lending in the UK and Spain as they are in Germany. Though large commercial banks dominate business lending in both countries, some (partly newly established) banks tend to specialise in lending to small enterprises at shorter distances there. To support short-distance lending, this paper suggests a compensation scheme for screening and monitoring costs. Such a scheme may stimulate banks to shift, or preserve, their lending decision processes to the regional level and reduce the need for standardisation, centralisation and bank mergers in times when interest rates are low.
Keywords: D43; E21; G01; G21; G38; R12; 330; comparing banking systems; SME finance in the UK; Spain and Germany; decentralised banking